ANALYSIS OF INTERNATIONALIZATION PROCESSES IN UKRAINIAN HIGHER EDUCATIONAL INSTITUTIONS - Вербовська, Леся (SWorldJournal, 2025)
The article is dedicated to the current challenges faced by Ukrainian higher education institutions in modern conditions. The relevance of the study is timely, as internationalization processes require an understanding of external environmental dynamics a